Constructing anion vacancy-rich MoSSe/G van der Waals heterostructures for high-performance Mg–Li hybrid-ion batteries. Issue 40 (12th October 2021) - Yu, Xianbo; Zhao, Guangyu; Wu, Canlong; Huang, Huihuang; Liu, Chao; Shen, Xiaojie; Wang, Ming; Bai, Xiaoming; Zhang, Naiqing
Abstract : Anion vacancies riched MoSSe and graphene van der Waals heterostructures can reduce the ion diffusion barriers and increase the adsorption energy, thereby greatly enhancing the ion diffusion rate and suppressing the rapid voltage drop in discharge. Abstract : Compared with the strategy of expanding MoS2 interlayer spacing, constructing van der Waals heterostructures of MoS2 and graphene (MoS2 /G) has proven to be a more effective method to facilitate the ion diffusion rate in host materials. However, the reduced adsorption energy of intercalated metal ions at the active sites of MoS2 /G interlamination causes a rapid voltage drop during discharge processes, resulting in an inferior energy density. Herein, we constructed anion vacancy-rich MoSSe and graphene van der Waals heterostructures (v-MoSSe/G). By adjusting the Se doping amount, v-MoSSe/G with an S : Se ratio of 1 : 1 exhibits the most anion vacancies. Compared with MoS2 /G heterostructures, density functional theory calculations proved that more anion vacancies in v-MoSSe/G can further reduce the ion diffusion barriers and increase the adsorption energy of the intercalated ions, thereby greatly enhancing the ion diffusion rate and suppressing the rapid voltage drop during discharge processes. Therefore, for rechargeable Mg–Li hybrid-ion batteries, v-MoSSe/G realizes a Mg 2+ /Li + co-intercalation even at 1000 mA g −1, and also delivers excellent cycling performance, rate capability, and long-term cycling stability with a reversible capacity of 164.6 mA h g −1 at 1000 mA g −1 after 3000 cycles.